Biosilica‐Entrapped Enzymes Studied by Using Dynamic Nuclear‐Polarization‐Enhanced High‐Field NMR Spectroscopy. Issue 13 (12th August 2015) - Ravera, Enrico; Michaelis, Vladimir K.; Ong, Ta‐Chung; Keeler, Eric G.; Martelli, Tommaso; Fragai, Marco; Griffin, Robert G.; Luchinat, Claudio
Abstract Enzymes are used as environmentally friendly catalysts in many industrial applications, and are frequently immobilized in a matrix to improve their chemical stability for long‐term storage and reusability. Recently, it was shown that an atomic‐level description of proteins immobilized in a biosilica matrix can be attained by examining their magic‐angle spinning (MAS) NMR spectra. However, even though MAS NMR is an excellent tool for determining structure, it is severely hampered by sensitivity. In this work we provide the proof of principle that NMR characterization of biosilica‐entrapped enzymes could be assisted by high‐field dynamic nuclear polarization (DNP).